PENGGUNAAN DAN KONTEN INTERNET (Survai Aktifitas Penggunaan Perangkat dan Mediasi Konten Internet pada Masyarakat Kelurahan Rappojawa, Kecamatan Tallo, Kota Makassar) - Muhammad Rustam (BPSDMP Kominfo Jakarta, 2015)
The background of this research is the phenomenon of easyness of community to communicate since of ICT development, this article deals with phenomenon of the internet use, and access enabler, and mediating messages. This research uses the concept of activity within the concepts of Uses introduced by Levy in theoretical models of Uses and Gratifitcation. Data Collection is by survey. Based on the findings about the second dimension of activity phenomenon (communication sequence), especially in the second one, which concerns the applications phenomenon: browser; channel; and a variety of individual issues mediated by internet use. This existing diversity shows the selection process by respondents. In using media, individuals are assumed to be active selectors in the model of uses and gratification theory. This activation is caused by individuals, who are psychologically have needs and gratification. Thus, the emergence of diverse forms of activity, theoretically is possible because of the five alternative